Pelaksanaan Program Adiwiyata Pada Mata Pelajaran Al-Qur'an Hadits Di MTsN Tambakberas Jombang - Ali Muttaqin (Universitas KH. A. Wahab Hasbullah Tambakberas Jombang, 2017)
The prevention of environmental damage is not only be the government responsibility but also the society and education institutions, so in this case the government published Adiwiyata Programs for the schools. MTsN Tambakberas Jombang, as one of school which did that program by integrating the subject Al-Quran Al Hadits and living environment education. It consists of 5 issues are rubbish, energy, water, food, canteen, and biodiversity. The implementation of the learning through three steps: 1) plan the learning, 2) do the learning, 3) controlling and environmental care habit in school to be a student’s character.